Termination of employment and settlement in Indonesia - Eko, Suratin (2017)
Purpose - The purpose of this study looking for the role and position of workforce as an actor as well as the goal of development in Indonesia. Act no. 13 of 2003 on Manpower is made to ensure the maintenance of laborers/workers’ rights in an employment relationship, so that there is no cruelty from the stronger to the weaker.With the employment relationship, then the worker is entitled to wages in return for his work, while the employer/entrepreneur is entitled to the services/goods from the worker’s employment is in accordance with the agreed labor agreement. Termination of employment relationship between workers and employers should not be done arbitrarily.But there are certain things that must be fulfilled by both parties so that the layoffs do not harm the sense of justice between the two parties. The following will be described on layoffs and settlement.Methodology - This method research uses normative juridical method to find the rule of law, legal principles, and legal doctrines in order to answer the legal issues of legal problems faced by using the source of legal material in the form of primary legal material, secondary derived from legislation, law books, and other legal materials.Findings - The employment relationship may occur due to a contractual agreement either made in writing or orally. According to Article 1 point 14 of the Manpower Law, is a labor agreement is an agreement between the workers / laborers with employers or employer which contains the terms of employment, rights and obligations of the parties.With the employment relationship, then the worker is entitled to wages in return for his work, while the employer / entrepreneur is entitled to the services / goods from the worker’s employment is in accordance with the agreed labor agreement.Termination of employment relationship between workers and employers should not be done arbitrarily.But there are certain things that must be fulfilled by both parties so that the layoffs do not harm the sense of justice between the two parties.The following will be described on layoffs and settlement..